Soins à domicile en français. Rapport final - Atlantic Evaluation Group Inc (2013)

Recruiting doctors from and for underserved groups: Does New Brunswick's initiative to recruit doctors for its linguistic minority help rural communities? - Beauchamp, Jacinthe; Bélanger, Mathieu; Schofield, Aurel; Bordage, Rachel; Donovan, Denise; Landry, Michel (Canadian Journal of Public Health / Revue canadienne de santé publique, 2013)
Objectives Within health care, there are underserved groups. New Brunswick’s French-speaking minority, which also mostly lives in rural communities, is one such group. A physician shortage potentially prevents this population from accessing health promotion and clinical prevention services. This study analyzes whether New Brunswick Francophone doctors with rural backgrounds are more likely than doctors from urban regions to set up practice in rural communities of the province. Methods A questionnaire was sent to 390 New Brunswick Francophone physicians admitted in medicine between 1973 and 2000. It collected information on geographic origin and history of medical practice. Multivariate logistic regressions were used to identify whether a rural background is associated with the likelihood of ever and currently practicing in rural communities. We used the General Practice Rurality Index-simplified to quantify the rurality level of communities. Results In total, 264 (67%) physicians participated. A rural background was positively associated with the establishment of a first medical practice in a rural community. This relationship was only significant among family physicians. There was no statistically significant relationship between rurality of community of origin and rurality of current community of practice among either family or specialty physicians. Conclusion Although Francophone doctors with a rural background were more likely than their urban counterparts to set up their first practice in a rural community, this effect was not sustained. This raises questions as to why they leave rural communities and highlights the importance of measures to retain doctors as a way to promote public health for underserved rural groups.

Un regard sur la distribution des médecins de famille qui parlent français dans les communautés francophones de l’Ontario - Centre de recherche en santé dans les milieux ruraux et du nord (FOCUS sur la recherche [Université Laurentienne], 2013)
site internet de Focus sur la recherche: https://fr.cranhr.ca/focus

Examining the distribution of French speaking family physicians in Ontario’s Francophone communities - Centre for Rural and Northern Health Research (FOCUS on research [Laurentian University], 2013)
site internet de Research in focus: https://www.cranhr.ca/focus

Lignes directrices pour la formation des futurs professionnels de la santé et du service social - Dubouloz, Claire-Jehanne; Benoît, Josée; Guitard, Paulette; Brosseau, Lucie; Savard, Jacinthe; Drolet, Marie; Kubina, Lucy-Ann; Casimiro, Lynn (Groupe de recherche sur la formation professionnelle en santé et service social en contexte francophone minoritaire, 2013)

Les priorités de recherche sur la santé des francophones en Ontario - Kalay, Anifa L.; Chomienne, Marie-Hélène; Farmanova, Elina (Revue canadienne de santé publique / Canadian Journal of Public Health, 2013)

Les professionnels de la santé et des services sociaux intervenant auprès des francophones minoritaires : l’enjeu du capital social - Savard, Sébastien; Arcand, Isabelle; Drolet, Marie; Benoît, Josée; Savard, Jacinthe; Lagacé, Josée (Francophonies d’Amérique, 2013)
Cet article présente les résultats d’une recherche qualitative sur la collaboration et le partenariat entre les professionnels des services sociaux et de la santé qui interviennent auprès de francophones vivant en situation minoritaire en Ontario. L’étude met en lumière, à partir de l’information recueillie auprès de 43 professionnels rencontrés dans huit groupes de discussion, le contexte qui caractérise leur pratique, les défis qu’ils rencontrent dans leur tentative de créer des liens de collaboration avec d’autres professionnels qui oeuvrent auprès des communautés francophones minoritaires ainsi que les facteurs qui facilitent l’établissement de partenariats entre les différents intervenants qui répondent aux besoins de cette population. Les résultats font ressortir que le sentiment d’appartenance, la confiance et l’engagement des professionnels envers la communauté francophone, de même que les valeurs de réciprocité et de solidarité qui les habitent sont des éléments qui favorisent le développement du capital social de la communauté des intervenants. Cependant, le manque de mécanismes permettant la consolidation et la pérennisation des relations de collaboration constitue un facteur qui limite la capacité de bonifier le capital social des professionnels de la santé et des services sociaux francophones et bilingues.

Promising quantities, disappointing distribution. Investigating the presence of French-speaking physicians in Ontario’s rural francophone communities - Timony, Patrick; Gauthier, Alain; Hogenbirk, John. C.; Wenghofer, Elizabeth (Rural and Remote Health, 2013)
Introduction: Previous studies have suggested that there may be a lack of French language healthcare services in the province of Ontario. The purpose of this study was to determine if physicians in Ontario who expressed a proficiency in providing services in the French language are located in 'Francophone communities'. Method: Responses from 10 968 Ontario-based family physicians (FPs) certified by the College of Family Physicians of Canada and uncertified general practitioners (GPs) who responded to the 2007 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey were analysed and compared to the 2006 census of the population of Ontario. Main outcome measures were the number of FP/GPs categorized by their language of competency to conduct medical practice and the number of people categorized by their first official language spoken. The physician-to-population ratio was then compared for different groups of communities in Ontario categorized by the degree of francophonie of the community: strong French communities, with a Francophone population ≥25%; moderate French communities, with a Francophone population of 10-24%; and weak/no French communities, with a Francophone population <10%. Results: There are 5.6 French speaking FP/GPs for every 1000 Francophones in communities with a French population less than 10%. This ratio is considerably greater than what was found in moderate French communities (3.4 FP/GPs) and strong French (1.3 FP/GPs). Overall the lowest ratios were found in rural strong French communities both in southern and northern Ontario (0.8 FP/GPs and 0.9 FP/GPs respectively). The ratio for all of Ontario was 0.7-1.3. Conclusions: As the number of Francophones increases in a community, the availability of French-speaking FP/GPs actually decreases, particularly in rural northern Ontario. Furthermore, there is a paradoxical relationship between the potentially high number of FP/GPs in the province with French-language capabilities and the perceived deficiencies in the availability of French language medical services. Key words: family physician, Francophone community, general practitioners, health and human resources, language, physician-patient ratios, urban. Introduction